Pembelajaran Matematika Melalui Strategi Problem Based Learning Dan Discovery Learning Ditinjau Dari Keaktifan Siswa Terhadap Hasil Belajar Siswa Kelas Viii Semester Genap SMP Negeri 2 Kartasuratahun Ajaran 2014/2015 - Yuliana, Yuliana, Dr. Sumardi, M.Si (2015)
Abstract: This study aims to determine: (1) The effect of learning srategy between Problem Based Learning and Discovery Learning on learning outcomes (2) The effect of the activity on learning outcomes (3) The interaction between learning strategy and the liveliness of the mathematics learning outcomes. This study was an experimental study. The population in this study the entire eighth grade students of SMP Negeri 2 Kartasura Academic Year 2014/2015. The sample of this study, VIIID class as a class experiment with 32 students and classes VIIIF as a control class with 30 students. The sampling technique is done by cluster random sampling technique. Data collection method used is the method of tests and questionnaires as the principal methods and documentation as an auxiliary method. The analysis technique used is a two-way analysis of variance test different cells previously performed using methods Liliefors normality test and homogeneity test using Bartlett method. Based on the research results with α = 5%, was obtained (1) There are differences in problem-based learning strategies and Discovery Learning on learning outcomes with FA = 8,6536 > Ftabel =4,016 (2) There is the effect of the activity on learning outcomes with FB = 9,7383 > Ftabel = 3,166 (3) There is no interaction between learning strategy and the activity on learning outcomes with FAB = 0,7452 < Ftabel = 3,166.